Effect of Silane Treatment on Mechanical Properties of Basalt Fiber/Polylactic Acid Ecofriendly Composites - Kurniawan, Denni; Kim, B.; Lee, H.; Lim, J. (Taylor & Francis, 2013)
Ecofriendly thermoplastic composites combining basalt fiber and polylactic acid were prepared and analyzed, considering effects when the fiber is silane treated. Intended to improve mechanical properties of the composites, the silane treatment varied the types of silane solution (water- and methanol-based solvents) and immersion time (15 and 60 min). Optimum mechanical properties were exhibited by composite whose basalt fiber constituent was treated by silane dissolved in water-based solvent, for a short period of time. © 2013 Copyright Taylor and Francis Group, LLC.